Draft Seventh Five Year Plan and Annual Plan 1985-86 Government of Mizoram - Planning Commission (Planning Commission, 1985)
To step up managerial efficiency, it is envisaged to place trained, full time, paid Secretaries through the induction of greater able to be played by the Cadre Management Society and provision of manager to subsidy during the plan period.
Government of Mizoram, Department of Co-operation